Exploration of the use of PBL and interactive videos in developing thinking student criticism - Irwan Putra; Maimun Maimun; Izza Madani (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2026)
The 21st century is characterised by rapid technological advancements that necessitate a transformation in pedagogical approaches, particularly concerning the cultivation of students' critical thinking skills. Within the context of Citizenship Education, critical thinking serves as a fundamental competency for the reflective and rational examination of socio-civic issues. However, the persistent dominance of conventional didactic methods frequently results in student disengagement and diminished academic participation. Consequently, this descriptive qualitative study aims to explore the integration of the Problem-Based Learning (PBL) model with interactive video technology to enhance students' critical thinking capabilities. Data were gathered via in-depth interviews with ten students and subsequently analysed through systematic stages of data reduction, data display, and conclusion verification. The findings indicate that the synergistic application of PBL and interactive video fosters a more active, contextualised, and reflective learning environment. Students demonstrated discernible improvements across four dimensions of critical thinking: analysing issues using visual scaffolding, formulating collaborative solutions, deducing logical conclusions grounded in theoretical frameworks and social realities, and evaluating arguments ethically and contextually. Ultimately, these results suggest that integrating PBL with interactive video significantly facilitates the comprehensive development of students' critical cognitive patterns.